The association between urinary cotinine level and metabolic syndrome profiles among adolescents: findings from the Ewha Birth and growth study - Hyunjin Park; Ui-Jeong Kim; Eun Jeong Choi; Seunghee Jun; Bomi Park; Hye Ah Lee; Hae Soon Kim; Hyesook Park (BMC, 2023)
Abstract Background: Secondhand smoke (SHS) exposure among adolescents who are still developing can negatively affect their physical and psychological health, including metabolic syndrome (MetS), which is a risk factor for cardiovascular disease. However, the relationship between exposure to SHS and MetS in adolescence has not been evaluated. Methods: A total of 240 subjects aged 13-15 years who were followed up in the Ewha Birth and Growth Study were included in this study. Using the urinary cotinine level, the participants' exposure to SHS was divided into tertiles, and the continuous MetS score (cMetS) and its components were compared among the three groups using a generalized linear model and trend analysis. Univariate and multivariate linear regression analyses were performed. We adjusted for several confounding variables including sex, father's education level, father's current alcohol consumption status, moderate physical activity, and overweight status. Results: The association between cMetS and the urinary cotinine level was not significant. However, the higher the urinary cotinine level, the lower the high-density lipoprotein cholesterol (HDL-C) level. In particular, the significance of the HDL-C level was maintained after adjusting for covariates. Conclusions: This study supports an association between SHS exposure and the components of MetS in adolescents aged 13-15 years, and it suggests the need to address SHS exposure in adolescents to reduce the cardiovascular risk in later life.